From fear to fraternity : a Russian tale of crime, economy and modernity - Rawlinson, Patricia (Pluto ; Distributed in the USA by Palgrave Macmillan, 2010)
A unique analysis of the development of Russian organised crime. The end of communism marked the re-emergence of a huge rise in organised crime across Russia and Eastern Europe. High-profile efforts to combat it have met with little success.